2015
DOI: 10.1016/j.comcom.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A distributed demand-side management framework for the smart grid

Abstract: This paper proposes a fully distributed Demand-Side Management system for Smart Grid infrastructures, especially tailored to reduce the peak demand of residential users.In particular, we use a dynamic pricing strategy, where energy tariffs are function of the overall power demand of customers. We consider two practical cases: (1) a fully distributed approach, where each appliance decides autonomously its own scheduling, and (2) a hybrid approach, where each user must schedule all his appliances. We analyze num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…DISTRIBUTED DSM: PROBLEM FORMULATION AND GAME MODEL In this paper, we consider a fully distributed demand-side management framework based on a non-cooperative game theoretical approach [21]. This framework is designed to efficiently schedule the electric appliances of a group of residential consumers, H, over a 24-hour time period divided into a set, T , of time slots.…”
Section: Related Workmentioning
confidence: 99%
“…DISTRIBUTED DSM: PROBLEM FORMULATION AND GAME MODEL In this paper, we consider a fully distributed demand-side management framework based on a non-cooperative game theoretical approach [21]. This framework is designed to efficiently schedule the electric appliances of a group of residential consumers, H, over a 24-hour time period divided into a set, T , of time slots.…”
Section: Related Workmentioning
confidence: 99%
“…the standard deviation is so low that the addition of noise to the scheduled consumption profiles leads to negligible alterations and intuitively provides no privacy preservation), in order to show the net effect of the privacyfriendly protocol on the performance of the DSM. Notice that the comparison between the performance of the proposed load scheduling game and the benchmark case without demandside management has already been presented and discussed in [34], where it is shown that the electricity bill and the peak demand decrease by as much as 55% with respect to the case without DSM and that this gain is influenced by the appliances flexibility and householders preferences.…”
Section: B Performance Evaluation: Test Case Amentioning
confidence: 99%
“…Different from T2.1 D-V, the responsibilities of control elements in this category are symmetrical, and the functions being executed in the control elements are similar. Examples are [45]- [48]. The categories introduced so far are illustrated in Fig.…”
Section: Architecturesmentioning
confidence: 99%
“…In T2.2.A D-H-(C)entralized shared memory, a single entity is available to relay information among control elements as an essential part of the control algorithm (e.g. [45], [46]). In contrast T2.2.B D-H-(P)2P represents only fully distributed P2P control architecture, as for example in [47], [48].…”
Section: Architecturesmentioning
confidence: 99%